Optimization of ultrasonic assisted extraction (UAE) of bioactive from napier grass (Pennisetum purpurcum) and evaluation of their bioactivity, antimutagenicity and cytotoxicity - Konkanok Thaisungnoen; Anal, Anil Kumar; Loc Thai Nguyen; Sadiq, Muhammad Bilal; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
Napier grass ( Pennisetum purpureum ), a perennial grass of the Poaceae family, was found the fluctuated antioxidant and antimicrobial properties under different growth period and different age of the grass. Ultrasound assisted extraction was applied for the extraction of bioactive constituents from napier grass in which ethanol was used as solvent. The optimization of the ultrasonic - assisted extraction conditions for bioactive compounds from napier grass of different growth period (50, 70 and 90 days) was studied. The quantitative proximate analysis indicated that the 50 days of napier grass provided high protein content ( 14.88 % w/w). The effect of three independent variables; ethanol concentration, volume of solvent used and extraction time on the total phenolic content, total flavonoid content, antioxidant activity as scavenging activity of 1,1 - diphenyl - 2 - picrylhydrazyl (DPPH) radical and ferric reducing antioxidant power (FRAP) assay and reducing power and antimicrobial activities was determined by response surface methodology (RSM) together with Box - Behnken design. The 50 days of napier grass presented more effectiveness of antioxidant and antimicrobial properties than the others. The point with ma ximum desirability of 0.575 at 47.68%, ( v/v ) of ethanol, 10 ml solvent per g of sample and 50 min of extraction was selected as the optimum condition for extraction of bioactive compounds from napier grass. Under these condition, the total phenolic content , total flavonoid content, antioxidant activity as % DPPH, antioxidant activity as FRAP and reducing power were 10.984 mg GAE/ g, 6.51 mg QE/g, 82.867 %, 143.058 omol/g and 7.604 mg AAE/g respectively. The diameter of inhibition zone of Staphyloccocus aureus , Escherichia coli , Salmonella spp. and Aspergillus niger presented 16.258, 17.87, 14.794 and 29.08 mm, respectively. The minimum inhibitory concentration and minimum bactericidal concentration values of bioactive extracts against Escherichia coli and Salmonella spp. showed 75 mg/mL and 150 mg/mL respectively while the minimum inhibitory concentration and minimum bactericidal concentration value of Staphylococcus aureus showed 37.5 mg/mL and 75 mg/mL, respectively. The minimum inhibitory concentration and minimum fungicidal concentration value against Aspergillus niger showed 37.5 mg/mL and 75 mg/mL, respectively. In this study, the napier grass extract provided strong antimutagenicity as well as the napier grass extract (75 mg/mL) was demonstrated to inhibit Salmonella spp. in chicken meat used as challenge study. The effect of napier grass extract on Vero cells and Caco - 2 cells indicated non - cytotoxicity
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2017
Keywords: Pennisetum purpureum; Bioactive compounds -- Biotechnology; Ultrasonic waves